OTHER'S MOTIVATION TO BRING TODDLERS TO POSYANDU TIBAN INDAH VILLAGE, SEKUPANG HEALTH CENTER WORK AREA - Magfirah Al'amri; Sarita Miguna (Universitas Batam, 2021)
Background :Toddlers are a period of rapid body and brain growth in achieving optimal functions. Posyandu is a community health facility managed independently by the community. The research objective was to determine whether there was a relationship between motivation and the behavior of mothers bringing toddlers to Posyandu in the Tiban Indah Village, the working area of the Sekupang Health Center, Batam City. Toddlers are a period of rapid body and brain growth in achieving optimal functions. Posyandu is a community health facility managed independently by the community. The research objective was to determine whether the motivation of mothers to bring toddlers to Posyandu in the Tiban Indah Village, the Working Area of the Sekupang Health Center, Batam City in 2017. Method :The design of this research is a descriptive study. The population in this study were all households with toddlers aged 1-5 years as many as 1,420 children under five, with a total sample of 312 respondents, using purposive sampling technique. The research was conducted in the Sekupang Health Center, Batam City. Result : It can be seen from 312 respondents, it can be seen that as many as 130 respondents (41.7%) have high motivation, and 182 respondents (58.3%) have low motivation to visit Posyandu in Tiban Indah Village, Sekupang Health Center, Batam